A new species of akodon (rodentia, cricetidae) from the northern campos grasslands of argentina - Pardiñas, Ulises Francisco J. (2005)
Integrated analyses of morphological, chromosomal, and molecular data resulted in the description of a new species of the genus Akodon, endemic to the Northern Campos in southern Misiones, Argentina. The new species presents a unique combination of characters, including a narrow zygomatic plate almost without a free upper border, short rostrum, short tail (40% of the head–body length), small and flat auditory bullae, diploid complement of 2n ¼ 36, and several molecular synapomorphies. Phylogenetic analysis, based on cytochrome b gene sequences, indicates that the Brazilian species Akodon lindberghi is sister to the new species, although this relationship is weakly supported. We comment on the conservation significance of our study, considering that these perisylvan grasslands are suffering substantial human disturbance by agriculture and burning practices.